Social Support and Healthcare Service Quality as Determinants of Treatment Interruption Among Drug-Resistant Tuberculosis Patients in Medan, Indonesia - Dalimunthe, Almira; Magdalena Sinaga, Bintang Yinke; Siagian, Parluhutan; Amelia, Rina (Jurnal Impresi Indonesia, 2025)
Indonesia ranks second globally in pulmonary TB cases after India, and drug-resistant TB remains a major cause of mortality in the country. Treatment adherence is influenced by multiple interacting factors, making dropout decisions a dynamic process. Early, targeted efforts to boost patient adherence and minimize loss-to-follow up are essential to prevent progression to more severe disease or death. This study aims to evaluate factors that lead to loss-to-follow up among drug-resistant tuberculosis patients in Medan, Indonesia. This research is a descriptive analytical study using a cross sectional approach. It was carried out at Adam Malik Hospital Medan on DR-TB patients who had been diagnosed bacteriologically. The data used were 104 patient subjects who met the inclusion and exclusion criteria. divided into groups who was loss in follow up and groups who completed treatment. The independent variables consist of social support and health care services. From the 104 research samples, 34 of them were DR pulmonary TB patients who was loss in follow up and 70 DR pulmonary TB patients who completed treatment. Bivariate analysis showed significant associations between loss-to-follow up and social support (p < 0.001; OR = 14.50), and healthcare service quality (p < 0.001; OR = 5.72). No significant association was found for age, sex, occupation, marital status, or family history of TB. In conclusion, social support and healthcare service quality play critical roles in determining adherence among DR-TB patients. Strengthening patient support networks and improving patient-centered healthcare delivery may help reduce treatment default rates.